1994
DOI: 10.1111/j.1365-2621.1994.tb02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of water uptake by citrus juices in powder form

Abstract: The water uptake of freeze-dried citrus juices (orange, tangerine and lemon) in powdered form was studied under different relative humidities (13 -98%) at 25°C. The empirical equation proposed previously by Pilosof et al. (1985) to predict water uptake by animal and vegetable proteins and starch materials was tested against the experimental results and good agreement was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
2
6
0
1
Order By: Relevance
“…As time increased, the sites became occupied, resulting in a decrease of the water sorptive capacity of the substrate. The time to reach equilibrium was approximately 120 h. Analogous results concerning the study of the kinetics of water uptake by food products have been reported by other investigators .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As time increased, the sites became occupied, resulting in a decrease of the water sorptive capacity of the substrate. The time to reach equilibrium was approximately 120 h. Analogous results concerning the study of the kinetics of water uptake by food products have been reported by other investigators .…”
Section: Resultssupporting
confidence: 86%
“…The kinetic sorption data were fitted to the Pilosof equation and kinetics parameter constants Q and B , as well as the correlation coefficient ( R 2 ) values were determined (Table ). This equation was also successfully applied by other investigators for the determination of water sorption kinetics in various substrates such as citrus juice powders , okara, a fibrous residue of soy base or soymilk production , and plantain flour .…”
Section: Resultsmentioning
confidence: 99%
“…The excipients used in the formulation typically have a low collapse temperature, which dictates the use of slow and conservative freeze-drying cycles. These slow and conservative cycles can be optimized by improving the rate of the mass transfer of water through the partially dried layer (Maia & Cal-Vidal, 1994). The mass transfer is usually expressed in the terms of resistance, with the dried product layer being responsible for almost 90% of the total resistance.…”
Section: Water Sorption Of the Peki Freeze-dried Pulpsmentioning
confidence: 99%
“…Of those models, the Peleg model (Peleg 1988) is the simplest and it has been applied to a variety of materials by many researchers (Sopade and Obekpa 1990;Sopade et al 1992Sopade et al , 1994Sopade and Okonmah 1993;Maharaj and Sankat 2000;Turhan et al 2002;Shittu et al 2004;Badau et al 2005). Pilosof et al (1985) developed a model for dehydrated food powders and Maia and Cal-Vidal (1994) evaluated its applicability to water uptake by citrus juice powder under different relative humidity conditions. To date, reports evaluating its applicability to food grains are few.…”
Section: Dynamic Water Adsorption Characteristics Of Distillers Driedmentioning
confidence: 99%